Elite Islamic Schools in Indonesia: Impact Analysis on Quality and Access to Education - Nanang Zakaria; Saiful Amin (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
The emergence of leading Islamic schools in Indonesia is highly anticipated by the Muslim community, as evidenced by the enthusiasm of parents to enroll their children in these prestigious Islamic schools. Until now, existing Islamic schools are perceived to lack the highest quality. The emergence of Islamic schools with good quality and readiness to compete is the desire of every Muslim family. However, unfortunately, in reality, these excellent Islamic schools are very expensive, so only families from the elite class can afford to enroll their children in them. As a result, these prestigious Islamic schools are more commonly known as Elite Islamic Schools. This research aims to analyze the phenomenon of the emergence of elite Islamic schools and their impact on the quality and access of education. The research method used in this study is literature analysis, which involves analyzing documents in the form of books, scientific journals, and other literature. The result of this research is the emergence of elite Islamic schools with breakthroughs and new innovations that make them superior and of good quality.